Effects of Tris on Responses of Human and Rabbit Platelets to Aggregating Agents - Packham, M A; Guccione, M A; Nina, M; Kinlough-Rathbone, R L; Mustard, J F (Thrombosis and Haemostasis, 1984)
Despite reports that Tris [tris(hydroxymethyl)aminomethane] affects platelets, it is often used to buffer suspending media. Human or rabbit platelets were washed and resuspended in Tyrode solution containing apyrase and 0.35% albumin. Addition of 15 mM Tris partially inhibited primary aggregation induced by 10 μM ADP and inhibited aggregation and release of 14C- serotonin from prelabelled platelets stimulated with low concentrations of thrombin (0.05-0.2 U/mL), or collagen. Platelets resuspended in 15 mM Tris, 0.15 M NaCl, 0.35% albumin, pH 7.5, did not aggregate in response to 10 μM ADP whereas platelets in Tyrode-albumin aggregated extensively. Ca2+ (5 mM) did not overcome the inhibition of thrombin-induced aggregation. Tris (15 or 1.5 mM) potentiated aggregation and release induced by sodium arachidonate (20-50 μM) or the ionophore A23187 (0.6-1 μM). Pretreatment of platelets with aspirin did not prevent potentiation by A23187, indicating that it is not mediated through activation of the arachidonate pathway. The inhibitory and potentiating effects of Tris are similar to those of amino sugars, lysine, arginine and primary amines such as methylamine and cadaverine, and may represent general effects of amines on platelets. Potentiation of the effects of some aggregating agents and inhibition of others re-emphasizes the concept that there are several different mechanisms through which aggregation can occur. Tris-based buffers are unsuitable for platelet suspending media and their use as solvents for aggregating agents or inhibitors should be limited.
Keywords: Tris; Platelet aggregation; Platelet suspending media; Platelet inhibitor; Potentiation of platelet aggregation